The Role and Response of the People of East Kalimantan Regarding the Transfer of the National Capital - Letty Dyastari; Adinda Alifah Candra (International Journal Of Education, Social Studies, And Management (IJESSM), 2022)
The purpose of this study is to discuss the role and response of the people of East Kalimantan regarding the transfer of the national capital. Collect data in this article using online questionnaires using google form, which is then analyzed using spss program version 21, previous research, and summarize the results of respondents' responses and take some information on the internet. Based on the results of the study, it is known that the number of people who are pro or agree with the government of the national capital is more than the people who counter or disagree with the number of people who agree, which is as many as 67 or 65.7% of the people. Meanwhile, based on the results obtained that the number of people who also consider that government planning related to the transfer of the national capital to East Kalimantan is a solution, with the number of people who responded that the transfer into a solution is as many as 58 communities as many as 58 people or 56.9%.